Enhancing EFL Students’ Listening Skills through Podcast-Based Instruction: A Quasi-Experimental Study in Indonesian Secondary Education - Intan Della Classica; Tri Rohani; Umi Kalsum (FOSTER: Journal of English Language Teaching, 2026)
This study investigates the impact of podcast-based listening activities on the listening comprehension skills of 11th-grade students at Muhammadiyah High School in Pagar Alam. While previous research has explored various multimedia tools in language learning, a gap remains in understanding how podcasts specifically enhance listening skills in secondary school settings. To address this gap, the study employs a quasi-experimental design with two groups: an experimental group of 30 students who participated in podcast-based listening activities, and a control group of 30 students who were taught using traditional listening exercises. Data were collected through pre-tests and post-tests to assess improvements in listening comprehension. The results indicate that the experimental group showed a significant improvement of 23.2%, compared to the control group's modest increase of 6.6%. These findings suggest that podcast-based activities can significantly enhance students' listening skills, providing a more engaging and flexible learning experience compared to traditional methods. The study’s implications include the potential for integrating podcasts into language curricula to offer students authentic, diverse listening exposure, thereby improving their overall listening proficiency.